Performance of the Alere Determine™ HIV-1/2 Ag/Ab Combo Rapid Test with algorithm-defined acute HIV-1 infection specimens - Parker, Monica M.; Bennett, S. Berry; Sullivan, Timothy J.; Fordan, Sally; Wesolowski, Laura G.; Wroblewski, Kelly; Gaynor, Anne M. (Journal of clinical virology, 2018)
•Determine Ag/Ab did not detect HIV-1 in 34% of serum samples from acute infections.•Instrumented Ag/Ab immunoassays are preferred over the Determine Ag/Ab rapid test.•Based on this study, further data on Determine Ag/Ab antibody sensitivity, including IgM detection, is warranted.•Further testing is suggested when reporting negative Determine Ag/Ab results on individuals with suspected acute infections. The capacity of HIV Antigen/Antibody (Ag/Ab) immunoassays (IA) to detect HIV-1 p24 antigen has resulted in improved detection of HIV-1 infections in comparison to Ab-only screening assays. Since its introduction in the US, studies have shown that the Determine HIV-1/2 Ag/Ab Combo assay (Determine Ag/Ab) detects HIV infection earlier than laboratory-based IgM/IgG-sensitive IAs, but its sensitivity for HIV-1 p24 Ag detection is reduced compared to laboratory-based Ag/Ab assays. However, further evaluation is needed to assess its capacity to detect acute HIV-1 infection. To assess the performance of Determine Ag/Ab in serum from acute HIV-1 infections. Select serum specimens that screened reactive on a laboratory-based Ag/Ab IA or IgM/IgG Ab-only IA, with a negative or indeterminate supplemental antibody test and detectable HIV-1 RNA were retrospectively tested with Determine Ag/Ab. Results were compared with those of the primary screening immunoassay to evaluate concordance within this set of algorithm-defined acute infections. Of 159 algorithm-defined acute HIV-1 specimens, Determine Ag/Ab was reactive for 105 resulting in 66.0% concordance. Of 125 that were initially detected by a laboratory-based Ag/Ab IA, 81 (64.8%) were reactive by Determine Ag/Ab. A total of 34 acute specimens were initially detected by a laboratory-based IgM/IgG Ab-only IA and 24 (70.6%) of those were reactive by Determine Ag/Ab. Due to their enhanced sensitivity, laboratory-based Ag/Ab IAs continue to be preferred over the Determine Ag/Ab as the screening method used by laboratories conducting HIV diagnostic testing on serum and plasma specimens.